Beyond food security: transforming the Productive Safety Net Programme in Ethiopia for the well-being of children - Tafere, Y; Woldehanna, T (Young Lives, 2012)
This paper investigates the possible impacts of the Productive Safety Net Programme (PSNP) on children’s well-being and recommends child-focused social protection that goes beyond the PSNP. It draws on data from the Young Lives survey of 569 rural households and qualitative case studies of 32 households and children living in four rural communities in 2006 and 2009. The quantitative analysis finds that, despite an increase in the incidence of economic shocks (such as drought and food-price inflation) and idiosyncratic family-related events such as the illness or death of family members, the value of cash and food transfers in real terms from the PSNP did not improve from 2006 to 2009, and even declined. Therefore the contribution of the PSNP to risk reduction is limited because transfers did not increase in the face of shocks. Moreover, the substitution effect of the Public Work component of the PSNP dominates the income effect and this has caused children to spend more time on paid and unpaid work. The survey data also show that the Public Work component did not increase the time children spent on schooling and studying at home, while the qualitative data suggested that it had a negative impact on their learning. Insufficiency of PSNP transfers forced households to send their children to work for wages. The schooling of children engaged in Public Work and wage labour has been affected, and in some cases they have been forced to drop out of school altogether. The existing PSNP could be improved in such a way that it provides Direct Support for schoolchildren so that their schooling may not be hampered. But we argue that the PNSP on its own cannot ensure children’s overall well-being. Though it protects many children from hunger, the PSNP fails to ensure food security, contributes little to poverty reduction and does not guarantee that children attend school. Ensuring children’s well-being and reducing their poverty require thinking beyond the PNSP. The paper concludes that, amid limited resources and contexts of vulnerability to protracted shocks, there is a need for child-focused social protection.